SCHOOL STRATEGY IN SHAPING THE CHARACTER OF GRADE V STUDENTS AT ELEMENTARY SCHOOLS (SDN 012 PASIR PENYU) DISTRICT INDRAGIRI HULU REGENCY - Mutiara Shinta; Siti Qurotul Ain (UNIVERSITAS PAKUAN, 2022)
This study aims to determine the school's strategy in shaping the character of fifth grade students at elementary schools (SD Negeri 012 Pasir Penyu), Indagiri Hulu Regency through the formation of religious, disciplined and caring character for the environment. The method used in this study is descriptive with a qualitative approach with steps of observation, interviews and documentation. The results of the study concluded that the school's strategic planning in shaping the character of fifth grade students seen from the planning was good, starting from activities inside and outside the classroom, adequate facilities and infrastructure to support the implementation of school strategies in shaping student character through the formation of religious characters, discipline and care for the environment.